Analisis Potensi Likuifaksi Menggunakan Data CPT (Cone Penetration Test) Studi Kasus Proyek Konstruksi Tangki Bahan Bakar di Masohi - Arifah Ismi Ambiya; Yerry Kahaditu Firmansyah; Bagas Aryaseta; Miguel Felix Wijaya (AGREGAT, 2026)
The Maluku Province is a region with high seismicity that is vulnerable to liquefaction hazards, particularly in coastal areas with shallow groundwater levels and saturated soil conditions. This study aims to analyze soil behavior indices and liquefaction potential at the construction site of a fuel tank in Masohi, Central Maluku, using Cone Penetration Test (CPT) by comparing the methods of Cetin (2004) and Idriss–Boulanger (2014), as well as comparing the results with previous research by Latifi et al. (2023) using the methods of Olsen (1997), Juang (2003), and Robertson (1998) under different soil conditions. The classification results indicate a dominance of silty clay soils that are potentially susceptible to liquefaction. In the Masohi case study, relatively similar CSR patterns were obtained; however, the Idriss–Boulanger (2014) method yielded higher CSR values compared to the Cetin (2004) method. The CRR analysis revealed significant differences; the Idriss–Boulanger method exhibits higher sensitivity to changes in soil type and parameters, whereas the Cetin method tends to produce more stable values. A similar finding was observed in the study by Latifi et al. (2023), which demonstrated that soil characteristics and calculation formulations result in varying analysis outcomes across methods regarding liquefaction potential as indicated by CRR values.